The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jcp.29266
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of UCA1 expression may be involved in the development of chemoresistance to cisplatin in the treatment of non‐small‐cell lung cancer via regulating the signaling pathway of microRNA‐495/NRF2

Abstract: Non-small-cell lung cancer (NSCLC) remains the leading cause of cancer death worldwide.As a platinum-based chemotherapeutic drug, cisplatin has been used for over 30 years in NSCLC treatment while its effects are diminished by drug resistance. Therefore, we aimed to study the potential role of UCA1 in the development of chemoresistance against cisplatin. Real-time polymerase chain reaction, western-blot analysis, and immunofluorescence were used to study the involvement of UCA1, miR-495, and NRF2 in chemoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…He et al [14] demonstrated that lncRNA UCA1 predicts a poor prognosis and regulates cell proliferation and migration in GC. Besides, UCA1 has been reported to promotes cisplatin resistance in Ovarian Cancer [13], non-small-cell lung cancer [12], oral squamous cell carcinoma [11] and bladder cancer [15], including GC [10]. Furthermore, it is reported that knockdown of UCA1 significantly promoted apoptosis by regulating Bax and cleaved caspase-3/9 expressions [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al [14] demonstrated that lncRNA UCA1 predicts a poor prognosis and regulates cell proliferation and migration in GC. Besides, UCA1 has been reported to promotes cisplatin resistance in Ovarian Cancer [13], non-small-cell lung cancer [12], oral squamous cell carcinoma [11] and bladder cancer [15], including GC [10]. Furthermore, it is reported that knockdown of UCA1 significantly promoted apoptosis by regulating Bax and cleaved caspase-3/9 expressions [8].…”
Section: Discussionmentioning
confidence: 99%
“…The caspase family is a protease system that directly causes the decomposition of apoptotic cells, which demonstrates an important role in the network of apoptosis mechanisms [7]. Many researches demonstrated that lncRNA UCA1 associates with the cisplatin resistance in a variety of tumors [10][11][12][13]. LncRNA UCA1, which is capable of controlling the activation of multiple signaling pathways in cancers, has been extensively researched in many tumors, including GC [10][11][12][13][14][15].…”
Section: Ivyspringmentioning
confidence: 99%
“…398,399 He et al 400 reported that UCA1 expression could predict a poor prognosis in patients, and it could also modulate GC cell migration and proliferation in vitro. It was also reported that UCA1 could increase cisplatin resistance in ovarian cancer, 401 non-small cell lung cancer, 402 oral squamous cell carcinoma, 403 bladder cancer, 404 and GC. 405 UCA1 knockdown was reported to increase apoptosis by modulating the expression of Bax and cleaved caspase-3/9.…”
Section: Lncrnas and Response To Chemotherapy In Gi Cancermentioning
confidence: 93%
“…UCA1/miRNA204-5p/cAMP responsive element binding protein-1 (CREB1) axis [ 17 ], UCA1/miRNA-143/Fos-like antigen 2 (FOSL2) axis [ 18 ], and UCA1/miRNA-196a-5p/CREB axis [ 19 ] were involved in enhancing the chemoresistance of colorectal, ovarian, and bladder cancers. In NSCLC, Li et al [ 20 ] discovered complementary binding sites between UCA1 and miRNA-495, and indicated that UCA1 promoted cisplatin resistance of NSCLC by regulating the miRNA-495/Nuclear factor-erythroid 2-related factor 2 (NRF2) axis as ceRNA. Liu et al [ 21 ] found that epithelial–mesenchymal transition (EMT) related proteins had changed and LUAD cell lines restored the sensitivity of cisplatin after UCA1 knockdown, which meant that UCA1 promoted cisplatin resistance by participating in the EMT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%